Developing energy performance standard, label and test procedures and impacts analysis for commercial chillers - Saidur, Rahman; Mahlia, T.M.I.; Hasanuzzaman, M. (Energy Education Science and Technology Part a-Energy Science and Research, 2011)
Chillers consume a major share of total air conditioning energy use in commercial and industrial buildings for space conditioning to get thermal comfort for a country. Experiences from other countries show that government intervention in the form of regulations such as mandatory and voluntary approaches can save huge amount of energy along with the reduction of emissions associated with energy have been quantified and presented. Emission reductions associated with the energy savings has been estimated and presented as well. Study also estimated the amount of avoided emissions along with the cost of avoided carbon. From the data analysis, it has been observed that energy efficient chillers can save huge amount of energy and utility bills. Based on review of international test standards, it has been found that ARI550/590 can be used for testing and rating of chillers energy performance. However, energy guide label is not suitable for information dissemination for chillers. Study estimated that 1688 MWh of energy and US108,040 bill can be saved for using energy efficient chillers.